4-Dimensional virtual reality model of Tetralogy of Fallot. (March 2022) - Perens, Gregory; Yoshida, Takegawa; Finn, J. Paul
Abstract: 3D imaging, modeling, and printing of congenital heart disease (CHD) have revolutionized the ability to visualize complex hearts. Printed 3D and virtual computer heart models have a number of limitations, including often lacking valve anatomy and representing only one time point in the cardiac cycle. 3D visualization of the beating heart has been limited to echocardiography, and multi-planar and topographical images from CT and MRI. Presented here are video capture images of a high resolution, dynamic 3D ('4D') model from a cardiac MRI study representing the endocardial surface "contracting" throughout the cardiac cycle in a 4 month old infant with Tetralogy of Fallot, double aortic arch, and vertical vein from the left upper pulmonary vein to innominate vein. Highlights: 3-Dimensional heart models may be created that contract throughout cycle. 3-Dimensional visualization of congenital heart models from inner endocardial perspective Advanced cardiac 4-dimensional imaging allows for contracting heart models.